Strength properties of extant hominoid hallucal and pollical metapodials. Issue 143 (June 2020) - Patel, Biren A.; Orr, Caley M.; Jashashvili, Tea
Abstract: Functional comparisons of cortical bone strength properties between hominoid hallucal and pollical metapodials (Mt1 and Mc1, respectively) are lacking. Determining which of these two elements is stronger, and by how much, could be informative because the hallux and pollex are used differently both within and among extant hominoids during locomotion and manipulation (i.e., functional differentiation between autopod pairs). Here, we compare Mt1 and Mc1 midshaft cortical area, polar section modulus, and polar second moment of area, calculated from high-resolution computed tomography images in humans ( n  = 21), chimpanzees ( n  = 47), gorillas ( n  = 24), orangutans ( n  = 20), siamangs ( n  = 8), and gibbons ( n  = 21). Intraindividual comparisons between bones within species were made using paired t-tests. Log10 -transformed Mt1:Mc1 ratios were created to assess relative strength asymmetry between bones, and interspecific comparisons of these proportions were made using analyses of variance. Absolute strength differences between the Mt1 and Mc1 for all variables were significantly larger in the Mt1 for all species ( p  < 0.05). Significant differences across species in Mt1:Mc1 proportions were also found, thereby demonstrating that strength asymmetry between bones differs among taxa ( p  < 0.05); asymmetry was lowest in orangutans, intermediate in gorillas, and greatest in humans, chimpanzees, siamangs, and gibbons. These findings support the hypothesis that the Mt1 is better adapted structurally than the Mc1 for bearing mechanical loads during weight support of locomotion in all extant hominoids and that pedal hallucal grasping likely engenders higher loads than manual pollical grasping in nonhuman hominoids. Thus, functional differentiation in autopod use within and among hominoids is reflected in hallucal and pollical metapodial strength properties.